Cattle price risk management strategies-using computer simulation to educate Iowa producers of available tools - Wray, Vicki Lorraine (Kansas State University, 2008)
Risk is an inevitable part of production agriculture. Price risk is especially a concern for cattle producers in the Midwest. Producers can curtail profit volatility, to an extent, through the utilization of price risk management strategies such as forward contracting, hedging, using put and call options, Livestock Risk Protection Insurance (LRP), as well as Livestock Gross Insurance (LGM) for feedlot cattle. Learning about such price risk management tools can be a daunting task. Kansas State University Extension created a computer based simulation workshop to assist them in teaching cattle producers about price risk management strategies. The simulation paralleled a lecture where participants learned of the price risk management strategies that are available. The simulation allowed the workshop participants to practice using the management strategies as they assumed the role of a feedlot or ranch manager in charge of marketing the operation's calves. In a cooperative effort with Iowa State University, Kansas State University presented the Cattle Risk Management Workshops across the state of Iowa. Participants were given pre-and posttests to measure the effectiveness of the workshop. The overall post-test scores were 25 percentage points higher than the pre-test scores. This research also discusses the interest and perceptions of cattle producers regarding price risk management strategies. The effectiveness of simulations as a teaching tool in helping producers learn about price risk management strategies is also reviewed. In addition, the various price risk management strategies available to producers, as well as seasonality of prices and basis are analyzed. This research also explains and estimates the LRP Feeder Cattle Basis Model. The LRP Feeder Cattle Basis Model was developed with the objective of assisting producers in forecasting LRP basis. The model was developed using similar methodology applied in the creation of a CME basis forecasting model developed by Kansas State University Extension and Custom Ag Solutions, Inc. The LRP Feeder Cattle Basis Model automatically adjusts for the LRP price adjustment factor applied to beef steer calves weighing less than 600 pounds, and beef heifers weighing 600-900 pounds. The LRP Feeder Cattle Basis Model explains 71.37 percent of the variation of LRP basis.
Keywords: Cattle price risk management strategies; Livestock risk protection insurance basis; Computer simulation; Economics, Agricultural (0503)